Pengukuran Tingkat Kesuksesan Penerapan E-Office Dengan Model Kesuksesan Sistem Informasi Delone Dan Mclean Di Dinas Perumahan Kawasan Permukiman Dan Pertanahan Kabupaten Sumedang - Vini Octaviani, Eneng; mahardika, fathoni; Hidayatul Akbar, Yopi (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2024)
The government's ability to develop the application of information technology is in accordance with Presidential Instruction (Inpres) No. 3 of 2003 concerning National E-Government Development Policies and Strategies which instructs to develop e-government in order to facilitate and facilitate government communication between one agency and the other. other agencies. Likewise, through Presidential Regulation No. 95 of 2018 concerning the Electronic-Based Government System (SPBE), that to realize clean, effective, efficient, transparent and accountable governance, as well as quality public services and an electronic-based government system is needed. The Department of Housing for the Settlement and Land Areas of Sumedang Regency has implemented e-office as an information technology that can manage administrative processes in its business processes. E-Office or Electronic Office is an application service to minimize the use of paper in electronic office administration aimed at office business processes, especially in official correspondence activities. The purpose of this study is to assess whether the implementation of the system is successful and has a positive impact on individuals and organizations. In this study, the authors chose the model provided by William H. DeLone and Ephraim R. McLean, which consists of six factors measuring the success of an information system, namely system quality, information quality, usage, user satisfaction and net benefits. Based on the results of data analysis and processing that has been carried out, it is found that the use of information technology, especially in the application of e-office at the Housing and Land Affairs Office of Sumedang Regency, can be said to have not been fully successful, this is indicated by six variables that obtained an average value. high and very high, but out of ten (10) hypotheses, four (4) were accepted and six (6) were rejected as a measure of the success of the information system.